Cerebrospinal fluid concentration of brain-derived neurotrophic factor and cognitive function in non-demented subjects. - Ge Li; Elaine R Peskind; Steven P Millard; Peter Chi; Izabela Sokal; Chang-En Yu; Lynn M Bekris; Murray A Raskind; Douglas R Galasko; Thomas J Montine (PLoS ONE)
Background Brain-derived neurotrophic factor (BDNF) is an activity-dependent secreted protein that is critical to organization of neuronal networks and synaptic plasticity, especially in the hippocampus. We tested hypothesis that reduced CSF BDNF is associated with age-related cognitive decline. Methodology/principal findings, and conclusions/significance CSF concentration of BDNF, Abeta(42) and total tau were measured in 128 cognitively normal adults (Normals), 21 patients with Alzheimer's disease (AD), and nine patients with Mild Cognitive Impairment. Apolipoprotein E and BDNF SNP rs6265 genotype were determined. Neuropsychological tests were performed at baseline for all subjects and at follow-up visits in 50 Normals. CSF BDNF level was lower in AD patients compared to age-matched Normals (p = 0.02). CSF BDNF concentration decreased with age among Normals and was higher in women than men (both p<0.001). After adjusting for age, gender, education, CSF Abeta(42) and total tau, and APOE and BDNF genotypes, lower CSF BDNF concentration was associated poorer immediate and delayed recall at baseline (both p<0.05) and in follow up of approximately 3 years duration (both p<0.01). Conclusions/significance Reduced CSF BDNF was associated with age-related cognitive decline, suggesting a potential mechanism that may contribute in part to cognitive decline in older individuals.